Verbascoside triggers apoptosis and ferroptosis in NSCLC by targeting BCAT2 - Ruijuan Li; Bin Li; Ping Wang (PLoS ONE, 2026)
Background The treatment of non-small cell lung cancer (NSCLC) has challenges such as drug resistance and recurrence. Concurrently, the induction of apoptosis and ferroptosis is a promising therapeutic strategy. This study aimed to investigate whether the natural product, verbascoside, induces apoptosis and ferroptosis in NSCLC cells by targeting BCAT2. Methods Bioinformatic analysis was used to predict the potential targets of verbascosides. Stable cell lines with BCAT2 knockdown and overexpression were constructed. The effects of verbascoside on NSCLC were evaluated in vitro and using a mouse xenograft model. Results Bioinformatics screening and molecular docking identified BCAT2 as a potential target of verbascoside, with a significantly stronger binding energy (−7.8 kcal/mol) than another candidate, PARP1. In vitro and in vivo experiments confirmed that BCAT2 knockdown significantly inhibited NSCLC cell viability, induced apoptosis and ferroptosis, and induced mitochondrial damage. Conversely, BCAT2 overexpression produced opposite effects. Verbascoside treatment inhibited BCAT2 expression in a concentration-dependent manner, recapitulating the apoptotic, ferroptotic, and mitochondrial damage phenotypes induced by BCAT2 knockdown; however, BCAT2 overexpression significantly reversed these effects of verbascoside. In an animal model, treatment with verbascoside significantly suppressed tumor growth and activated apoptosis and ferroptosis in tumor tissues by downregulating BCAT2. Conclusions Verbascoside can induce apoptosis and ferroptosis in NSCLC by directly targeting and inhibiting BCAT2, leading to mitochondrial dysfunction. This finding not only reveals BCAT2 as a novel target of verbascoside but also confirms its ability to induce apoptosis and ferroptosis in NSCLC cells.